2016
DOI: 10.1016/j.athoracsur.2016.03.093
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors Related to Symptomatic Venous Thromboembolic Events After Esophagectomy for Cancer

Abstract: Patients with ASA class III or IV and those who present a postoperative pneumopathy or ARDS seem to be at higher risk for VTE. Thus, current VTE screening and thromboprophylaxis for these patients might be inadequate and needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
(50 reference statements)
1
15
1
Order By: Relevance
“…In general, the overall 3.5% incidence of DVT/PE in our study was similar to the 2.9% (84 of 2,944) that noted in a large multicenter study that examined the incidence of postoperative symptomatic venous thromboembolic disease [23]. Interestingly, those investigators also found that a higher ASA class (III or IV), postoperative pneumonia, and acute respiratory distress syndrome were significantly associated with an increased risk of DVT/PE in a multivariate analysis [23]. Although we did not specifically evaluate for respiratory complications, our data did not show a significant relationship between a higher ASA class (III or IV) and DVT/PE.…”
Section: Commentsupporting
confidence: 88%
See 2 more Smart Citations
“…In general, the overall 3.5% incidence of DVT/PE in our study was similar to the 2.9% (84 of 2,944) that noted in a large multicenter study that examined the incidence of postoperative symptomatic venous thromboembolic disease [23]. Interestingly, those investigators also found that a higher ASA class (III or IV), postoperative pneumonia, and acute respiratory distress syndrome were significantly associated with an increased risk of DVT/PE in a multivariate analysis [23]. Although we did not specifically evaluate for respiratory complications, our data did not show a significant relationship between a higher ASA class (III or IV) and DVT/PE.…”
Section: Commentsupporting
confidence: 88%
“…The time frame of 30 days to observe thrombotic complications was chosen arbitrarily. There is no established consensus in the surgical literature for postoperative thrombosis, and studies have reported thrombotic complications from 1 up to 90 days after the operation [23,[28][29][30]. Some patients may have had small, asymptomatic pleural effusions after the operation, some of which may have been chylous.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the methods of diagnosis and treatment of PAPE have been continuously developed in recent years, including imaging diagnosis, interventional surgery and medicinal chemotherapy, the overall survival rate of patients with PAPE is extremely low. It was reported that the short-term mortality of patients with PAPE was between 10% and 23.1% [5][6][7][8][9]. Therefore, identifying the preoperative risk factors associated with mortality may help to direct more aggressive treatment strategies, such as brinolytic therapy, towards patients who will derive the greatest bene t.…”
Section: Introductionmentioning
confidence: 99%
“…Although the way of diagnosis and treatment of PAPE have been continuously developed in recent years, including imaging diagnosis, interventional surgery and medicinal chemotherapy, the overall survival rate of patients with PAPE was extremely low. It was reported that the short-term mortality of patients with PAPE was between 10% and 23.1% [5][6][7][8][9]. Therefore, identifying the preoperative risk factors associated with mortality may help to direct more aggressive treatment strategies towards patients who will derive the greatest benefit.…”
Section: Introductionmentioning
confidence: 99%